2018
DOI: 10.3389/fimmu.2018.00156
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein–Kinin System Suppresses Type I Interferon Responses: A Novel Pathway of Interferon Regulation

Abstract: The Kallikrein–Kinin System (KKS), comprised of kallikreins (klks), bradykinins (BKs) angiotensin-converting enzyme (ACE), and many other molecules, regulates a number of physiological processes, including inflammation, coagulation, angiogenesis, and control of blood pressure. In this report, we show that KKS regulates Type I IFN responses, thought to be important in lupus pathogenesis. We used CpG (TLR9 ligand), R848 (TLR7 ligand), or recombinant IFN-α to induce interferon-stimulated genes (ISGs) and proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 77 publications
1
27
0
1
Order By: Relevance
“…The increased aldosterone may be responsible for the hypokalemia seen in many COVID-19 patients. More speculatively, while the inflammatory arm of the RAS produces TNF, IL-6, and other pro-inflammatory cytokines without producing interferon, ACE cleaves bradykinin, a known suppressor of interferon, and so might lead to increased interferon in some individuals (Seliga et al, 2018). Some individuals with a particular genetic predisposition may produce high levels of interferon, and these may be the individuals who develop "COVID toes" (Landa et al, 2020;Zhang et al, 2020).…”
mentioning
confidence: 99%
“…The increased aldosterone may be responsible for the hypokalemia seen in many COVID-19 patients. More speculatively, while the inflammatory arm of the RAS produces TNF, IL-6, and other pro-inflammatory cytokines without producing interferon, ACE cleaves bradykinin, a known suppressor of interferon, and so might lead to increased interferon in some individuals (Seliga et al, 2018). Some individuals with a particular genetic predisposition may produce high levels of interferon, and these may be the individuals who develop "COVID toes" (Landa et al, 2020;Zhang et al, 2020).…”
mentioning
confidence: 99%
“…This may not indicate that IFNα is not playing a role, but rather the ability of the IFNAR antibodies to reach the brain and affect the CNS. Our recent work (13) shows that candidates of the (28). The effect of ACEi's, especially those that can cross the BBB, on microglial activation and cognitive effects have been demonstrated recently (19).…”
Section: Discussionmentioning
confidence: 95%
“…The effects of ACEi's have been very well described to act mostly via increasing the bioavailability of BK (18). We have earlier shown in murine bone-marrow-derived dendritic cells (BMDCs) that suppression of the IFN response by BK may be brought about, in part, via prostaglandins (13). We hypothesize that ACEi's potentiate bradykinin-mediated suppression of IFN responses in vivo through prostaglandins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While one may assume that the virus stimulates KLK13 production to promote the infection, this up-regulation is likely a natural response of the damaged tissue, as KLKs were previously reported to take part also in tissue regeneration ( 8789 ). Further, increased expression of KLKs may be the response to the inflammatory process, as Seliga et al demonstrated that KLK-kinin system is a potent modulator of innate immune responses ( 90 ).…”
Section: Discussionmentioning
confidence: 99%